2010
DOI: 10.1111/j.1600-0897.2010.00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide (LPS)-induced Interferon (IFN)-gamma Production by Decidual Mononuclear Cells (DMNC) is Interleukin (IL)-2 and IL-12 Dependent

Abstract: IL-2 and IL-12 up-regulated the production of IFN-γ in DMNC through increasing their susceptibility to LPS. TNF-α production is independent of such a mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 41 publications
(41 reference statements)
2
19
0
Order By: Relevance
“…Consistent with this observation, we also found Ber promoted IL-12 p40 production in LPS-challenged mice, which was inhibited by Y. It has been demonstrated that IL-12 upregulates IFN-γ regulation [25]. Thus, in this study, increased IFN-γ production by Ber in LPS-challenged mice may be related with enhanced IL-12 production, but the mechanism by which Ber plus Y promoted IFN-γ production in endotoxemic mice needs to be further investigated.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with this observation, we also found Ber promoted IL-12 p40 production in LPS-challenged mice, which was inhibited by Y. It has been demonstrated that IL-12 upregulates IFN-γ regulation [25]. Thus, in this study, increased IFN-γ production by Ber in LPS-challenged mice may be related with enhanced IL-12 production, but the mechanism by which Ber plus Y promoted IFN-γ production in endotoxemic mice needs to be further investigated.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that IFNγ plays a deciding role in whether immune cells attack and injure the CNS, and that LPS stimulates IFNγ production in immune cells3132. We thus questioned whether GA could reduce the phosphorylation of STAT1 and −3 via affecting the production of IFNγ or the activation of IFNγ receptor (IFNγR).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we showed a similar increase in IL-1RN, IL-6, IL-8, IL-10, IFN-g, and TNF production induced by LPS, consistent with previous studies. [33][34][35][36] We extended those observations to show that LPS also increased the secretion of other inflammatory-related cytokines, including proinflammatory cytokines IL-1B, IL-2, IL-12p70, IL-15, and IL-17A and anti-inflammatory cytokines IL-4, IL-9; chemokines MCP-1, MIP-1a, MIP-1b, RANTES, IP-10, eotaxin, and growth factors, CSF-3, CSF-2, and VEGFA. To our knowledge, this is the first description of secretion of these cytokines, chemokines, and growth factors in human decidual cells in response to LPS in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that LPS induces IL-1RN, IL-6, IL-8, IL-10, IFN-g, and TNF-a output from human choriodecidual tissues or cells in vitro, using a traditional enzyme-linked immunosorbent assay (ELISA). [33][34][35][36] Obviously, studies focused on the actions of individual cytokines may not be sufficient for understanding the mechanism of PTB related to infection or inflammation. Because many cytokines that accompany inflammation have closely related or overlapping biological effects and may be involved in different aspects of immune responses, quantitation of single cytokines may be of limited value.…”
Section: Introductionmentioning
confidence: 99%